Efforts To Improve The Quality of Bakcang Products in Surabaya Using The Quality Function Deployment (QFD) Method - Maria Bernadete Mulyono; Desrina Yusi Irawati (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Bakcang is a traditional Chinese food which is quite famous among the people of Surabaya. In the manufacturing process, bakcang still uses traditional methods using human expertise in a relationship regarding improving the quality of taste and appearance according to customer and company expectations. The stages of the Quality Function Deployment (QFD) method are carried out by making a House of Quality (HoQ) matrix. The results of the research are in the form of priority scales that must be improved for business development based on Voice of Customer. Improvements wrapping bakcang. Therefore, research was conducted to identify the quality characteristics of taste and appearance that are expected from both the consumer and company sides. The method used in this research is Quality Function Deployment (QFD). The distributed questionnaires will include the attributes of the respondent's classification, the level of importance, and the level of customer satisfaction. Then the results of data acquisition from filling out the questionnaire will be processed using the House of Quality (HoQ) method. The results of the study will show that there is to the output of HoQ are replacing packaging with other materials, providing labels as product information, making prints for more precise sizes, making cooking time guidelines so that the level of maturity is even, preparing fresh raw materials, utilizing social media, holding prices reductions, making new variations in the form of frozen, and opening new outlets with sufficient facilities.